Computer Vision Syndrome: Affecting Young and Old Alike - Anchit Wapa; Anu Namgyal (Delhi Journal of Ophthalmology)
The advancement in technology is no doubt a boon to the society, but it is also attached with a price that a person has to pay for it. In today's era, these amenities are an important part of everybody's lives from a young child to an adult. The digital devices in the form of computers, laptops, mobile phones, I-pads etc. are included in day to day lives of everyone, helping people achieve results much faster and has made our lives easy. When used in excess or in an improper way, these are associated with various health hazards like musculoskeletal and ocular complications. Ocular problems are reported as the most frequently occurring health problems among computer users. Here we report case of a young banker who was suffering from computer vision syndrome and after proper evaluation and guidance, she got better.